Rate of Union in Complex Distal Humerus Fractures Using Anatomically Contoured Locking Plates (Journal of Pakistan Orthopaedic Association, 2014)
Objective: A study to evaluate the rate of healing after open reduction internal fixation of complex distal humerus fractures using LCPs.Design: Observational study.Setting: Liaquat National Hospital, an orthopaedic trauma unit, which provides all the fracture care for a well-defined catchment population. Method and Material Patients/Participants: A consecutive series of 25 patients with distal humeral fractures admitted to the unit between July 2010 and April 2013.Intervention: We adopted a protocol of open reduction and fixation of all displaced intraarticular fractures (greater than 2 mm of displacement in any plane) in patients who were medically fit for anesthesia. Each case underwent osteosynthesis with distal humerus posterolateral and medial anatomically contoured locking plates via transolecranon approach using chevron osteotomy. 4mm partially threaded cancellous screw was used for augmenting intra-articular fragments in most cases. Postoperative immobilization was a back splint for 2 weeks. Elbow range of motion was started at 3 weeks. Radiological union, postoperative elbow range of motion and complications were recorded at 4 weeks, 8 weeks, 12 weeks and then at 6 months. Patients with open fractures, undisplaced fractures or who were medically unfit were excluded from this study.Results: Out of 25 patients included in this study, 11 (44%) were female and 14 (56%) were males, with male to female ratio of 1.27:1 .Our patients’ age ranged from minimum 18 years to maximum 50 years with the mean age of 37 years. The mechanisms of injury included falls from height in 4 patients and motorcycle or motor vehicle collisions in 21 patients. Right hand dominancy was noted in 17 patients out of 25 with gender difference of male to female ratio was 2.28:1 for right hand dominance and 1:1 in left hand dominance. Using AO classification, 5 fractures were classified as Type C1, 15 were Type C2 and 5 were Type C3. Operative time was average 75 minutes (ranged from 60 to 90 minutes). Union was achieved normally in 18 patients at 12 weeks and remaining 2 patients achieved delayed union at 18 weeks and 20 weeks. All the fractures were stable on healing. Complication of ulnar nerve neuroprexia was noted in 1 out of 25 patients, which got resolved in 5 months period. One patient required removal of intercondylar screw because of soft tissue impingement. On evaluating, mean arc of motion ranged from 10? to 120?. All patients achieved union with good range of motion and functional activity.Conclusions: Complex Intra or extra articular distal humerus fractures are a challenge to manage and require anatomical stable fixation. Anatomically contoured angular stable implants facilitate operative reduction and stabilization of the fracture and may allow early postoperative rehabilitation. Clinical and radiological results show good healing rate with reasonable range of motion.Key Words: complex distal humerus fracture, Anatomically contoured locking plates, open reduction and internal fixation, Intra-articular.